2009
DOI: 10.1523/jneurosci.3567-08.2009
|View full text |Cite
|
Sign up to set email alerts
|

Cerebral Microglia Recruit Monocytes into the Brain in Response to Tumor Necrosis Factorα Signaling during Peripheral Organ Inflammation

Abstract: In inflammatory diseases occurring outside the CNS, communication between the periphery and the brain via humoral and/or neural routes results in central neural changes and associated behavioral alterations. We have recently identified another immune-to-CNS communication pathway in the setting of organ-centered peripheral inflammation: namely, the entrance of immune cells into the brain. In our current study, using a mouse model of inflammatory liver injury, we have confirmed the significant infiltration of ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

19
535
2
12

Year Published

2009
2009
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 592 publications
(568 citation statements)
references
References 76 publications
19
535
2
12
Order By: Relevance
“…This process is controlled by cytokine and chemokine signaling and has been shown to affect brain microglia under conditions of inflammation remote to the CNS such as hepatic inflammation (Riazi et al ., 2008; D'Mello et al ., 2009). G3 mTerc −/− mice after 8 months of age start showing prominent signs of intestinal dystrophy and in extreme cases resulting in anal prolapse.…”
Section: Discussionmentioning
confidence: 99%
“…This process is controlled by cytokine and chemokine signaling and has been shown to affect brain microglia under conditions of inflammation remote to the CNS such as hepatic inflammation (Riazi et al ., 2008; D'Mello et al ., 2009). G3 mTerc −/− mice after 8 months of age start showing prominent signs of intestinal dystrophy and in extreme cases resulting in anal prolapse.…”
Section: Discussionmentioning
confidence: 99%
“…This suggests an influence of the immune system on the brain during increased disease activity (3). Studies in patients with multiple sclerosis and in animal models of autoimmune inflammation of the CNS have shown that increased choline signals, as a marker of cell membrane turnover, are associated with inflammation in the form of monocyte infiltration, rather than demyelination (9,19).…”
Section: Discussionmentioning
confidence: 99%
“…The median number of disease-modifying antirheumatic drugs (DMARDs) taken at the time of the study and previously taken was 3 (range [1][2][3][4][5][6]. DMARD treatment at the time of the study was as follows: infliximab in 1 patient, methotrexate in 22, sulfasalazine in 8, leflunomide in 4, aurothiomalate in 1, azathioprine in 1, and antimalarial drugs in 4.…”
Section: Methodsmentioning
confidence: 99%
“…The activated microglia produce MCP-1/ CCL2 prior to cerebral monocyte infiltration in response to peripheral TNF-a signaling and in TNF-R1 deficient mice microglial expression of MCP-1/CCL2 and cerebral monocyte recruitment were both markedly inhibited. 74 A whole human genome micro-array approach in post mortem brain samples from cirrhotic patients with or without HE and non-cirrhotic controls, has indicated altered expression levels in over one thousand genes related to oxidative stress, microglial activation, receptor signaling, inflammatory pathways, cell proliferation and apoptosis. Despite an up-regulation of genes associated with microglia activation, proinflammatory cytokine mRNA profiles remained unchanged in the brain of patients with liver cirrhosis and HE as compared to controls supporting the previous findings of the Zemtsova study.…”
Section: The Role Of Systemic Inflammation In Encephalopathy In Chronmentioning
confidence: 99%